Information manipulation on TikTok and its relation to American users' beliefs about China - Finkelstein, Danit; Yanovsky, Sonia; Zucker, Jacob; Jagdeep, Anisha; Vasko, Collin; Jagdeep, Ankita; Jussim, Lee; Finkelstein, Joel (Frontiers in Social Psychology, 2025)
Three studies explored how TikTok, a China-owned social media platform, may be manipulated to conceal content critical of China while amplifying narratives that align with Chinese Communist Party objectives. Study I employed a user journey methodology, wherein newly created accounts on TikTok, Instagram, and YouTube were used to assess the nature and prevalence of content related to sensitive Chinese Communist Party (CCP) issues, specifically Tibet, Tiananmen Square, Uyghur rights, and Xinjiang. The results revealed that content critical of China was made far less available than it was on Instagram and YouTube. Study II, an extension of Study I, investigated whether the prevalence of content that is pro- and anti-CCP on TikTok, Instagram, and YouTube aligned with user engagement metrics (likes and comments), which social media platforms typically use to amplify content. The results revealed a disproportionately high ratio of pro-CCP to anti-CCP content on TikTok, despite users engaging significantly more with anti-CCP content, suggesting propagandistic manipulation. Study III involved a survey administered to 1,214 Americans that assessed their time spent on social media platforms and their perceptions of China. Results indicated that TikTok users, particularly heavy users, exhibited significantly more positive attitudes toward China's human rights record and expressed greater favorability toward China as a travel destination. These results are discussed in context of a growing body of literature identifying a massive CCP propaganda bureaucracy devoted to controlling the flow of information in ways that threaten free speech and free inquiry.